An Exploration of How Biophilic Attributes on Campuses Might Support Student Connectedness to Nature, Others, and Self - Alves, Susana; Betrabet Gulwadi, Gowri; Nilsson, Pia (Frontiers in Psychology, 2022)
University Campuses remain important settings for nurturing and supporting student health and quality of life. Contact with nature plays a vital role in students’ health and quality of life (QoL) allowing them to cope with mental fatigue, stress and a constant need for restoration. Research shows that the health benefits of nature experience may be facilitated by campus spaces and activities that afford connectedness. However, we still lack an integrative conceptual framework to frame the mechanisms involved in achieving connectedness for making recommendations for campus design. In this paper, we examine students’ connectedness in campus settings in relation to biophilic elements and attributes. We aim to understand how both direct and indirect pursuits in nature and also place-based experiences on campus foster connectedness and consequently impact students’ health and QoL. Our analysis shows that connectedness seen through the lens of Kellert’s biophilic design principles and aided by Alexander’s pattern language provides a relational and long-term perspective on recommending strategies for connecting students to nature, to others, and to themselves in campus settings.